Manifestations of Theory of Mind (ToM) in Primary School Students During Art Appreciation Sessions - Mendonça, Pedro; Mayrand, Julie (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2025)
Theory of Mind (ToM) is the cognitive ability to understand one’s own and others’ mental states, recognizing that others have unique beliefs and perspectives. This study uniquely integrates Visual Thinking Strategies (VTS) with ToM development, offering a novel approach to understanding how art appreciation can enhance cognitive and socio-emotional skills in primary school students. By examining both cognitive and affective dimensions of ToM across diverse socio-cultural contexts, this research provides a comprehensive analysis that bridges gaps in existing literature on art education and cognitive development. The findings have significant practical implications, suggesting that incorporating VTS into the curriculum can foster empathy, perspective-taking, and critical thinking, thereby contributing to a more inclusive and supportive classroom environment.